PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Infrastruktur, Utilitas dan Transportasi Sub Sektor Transportasi yang Terdaftar Pada Bursa Efek Indonesia Pada Tahun 2017-2019) - Saputra Ilham; Andreas Andreas; Azhar A Al (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to test and analyze: 1) the effect of audit committee expertise on earnings management, 2) the effect of the audit committee size on earnings management, 3) the effect of the frequency of audit committee meetings on earnings management. The population used in this study is a transportation company listed on the Indonesia Stock Exchange in 2017-2019. Samples were determined using purposive sampling method and obtained samples from 33 companies. The type of data used in this study is secondary data. Data analysis is done by multiple regression analysis using SPSS program. This research uses 2 methods of calculating earnings management, namely accrual and riil. Accrued results of this study show that: 1) the expertise of the audit committee affects earnigs management (sig=0.001; sig≤0.05), 2) the size of the audit committee has no effect on earnings management (sig=0.385; sig≤0.05), 3) the frequency of audit committee meetings affecting earnings management (sig=0.046; sig≤0.05). In riil terms, the results of this study show that: 1) the expertise of the audit committee affects earnings management (sig=0.013; sig≤0.05), 2) the size of the audit committee affects earnings management (sig=0.004; sig≤0.05), 3) the frequency of audit committee meetings affects earning management (sig=0.034; sig≤0.05).Keywords: Expertise of the Audit Committee, Size of Audit Committee, Frequency of Audit Committee Meetings, Earnings Management.